Group mentoring of youth scientists to enhance the students’ research literacy - Ahmad Fauzi; Lud Waluyo; Diani Fatmawati; Siti Zubaidah; Sitaresmi Weka Sukrisno; Nafisa Nur Azizah (Universitas Muhammadiyah Malang, 2023)
The Youth Scientific Group (YSG) is an extracurricular activity that has a positive impact on students. Unfortunately, the presence of YSG in various schools, including SMAN 1 Tumpang, is still not optimal. In this high school located in Malang Regency, the YSG activities have not been carried out consistently. The scientific competence and research literacy of students at SMAN 1 Tumpang have not been fully utilized. In response to this issue, the aim of the Community Science and Technology Program (Community Service Program) is to enhance the scientific competence and literacy of students at SMAN 1 Tumpang through mentoring in the preparation of YSG. This Community Service Program consists of several stages, including observation and problem identification, preparation of YSG mentors, material presentation, training and mentoring, activity evaluation, and the preparation of scientific articles as program outputs. The average pretest score of the students' knowledge was 39.67, while the posttest score increased to 93.23. The average N-gain of their knowledge reached 0.836. Based on this N-gain value, the students' knowledge improvement is categorized as high. The paired t-test results indicate a significant difference in students' knowledge related to scientific work before (M = 39.7, SD = 20.6) and after the program (M = 93.2, SD = 7.5), t(30) = 14.6, p < .001. Therefore, the program implemented in the partner school has proven to be beneficial in enhancing students' scientific competence.